2002
DOI: 10.1093/bja/88.6.803
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐emptive effect of epidural sufentanil in abdominal hysterectomy

Abstract: We conclude that pre-emptive analgesia with epidural sufentanil was associated with a short-term sufentanil-sparing effect, and could have reduced stress hormone responses and wound sensitization after abdominal hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
(19 reference statements)
2
12
0
Order By: Relevance
“…The postoperative first VAS pain score was importantly lower in the bupivacaine group than in the tramadol group. The result supports studies which indicated the superiority of local anesthetics when compared with intra-or suprathecal opioids for preemptive analgesia [32,33,42]. All the other VAS values of the bupivacaine group were significantly lower than in the tramadol group during the study with an insignificantly different supplementary demand dose requirement.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The postoperative first VAS pain score was importantly lower in the bupivacaine group than in the tramadol group. The result supports studies which indicated the superiority of local anesthetics when compared with intra-or suprathecal opioids for preemptive analgesia [32,33,42]. All the other VAS values of the bupivacaine group were significantly lower than in the tramadol group during the study with an insignificantly different supplementary demand dose requirement.…”
Section: Discussionsupporting
confidence: 84%
“…Preemptive effect of opioids especially in small doses is still controversial [32,33]. Anti-analgesia with increased side effects in the postoperative period was previously demonstrated with preincisional administration of lowdose (20 mg) bolus epidural tramadol when compared with 100 mg and placebo administrations [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several classes of analgesics have been utilized in the treatment of post-operative pain. At this respect, several clinical studies have demonstrated the effectiveness of NSAIDs (Liu et al, 2005;Karaman et al, 2006) and opioids (Akural et al, 2002;Yoshimoto et al, 2005) in pre-emptive analgesia. In addition, most of these drugs have side-effects, which limit their use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal morphine seems to attenuate several measures of the surgical stress response, in particular serum values of catecholamines and glucose . However, preoperative intravenous morphine fails to attenuate the stress response measured by serum cortisol, glucose and leukocytes (Kilickan, 2001); the socalled "preemptive effect" has been largely abandoned in clinical life because many studies fail to document better pain relief when opioids are administered preoperatively than postoperatively, even though studies appear from time to time arguing the case of preemptive analgesia from the viewpoint of minor effects on immune function, parameters which may be clinically redundant (Akural, 2002;Akural, 2004).…”
Section: Opioid-free Analgesiamentioning
confidence: 99%